Case report: DKRd regimen in the treatment of newly diagnosed POEMS syndrome and literature review - Wang, Jianchao; Liao, Wensheng; Liu, Zhongwen; Kong, Dai (Frontiers in Oncology, 2024)
POEMS syndrome, characterized as a rare multisystem paraneoplastic syndrome, arises from plasma cell abnormalities. Coined by Bardwick in 1980, the acronym POEMS delineates the distinctive features of the syndrome: Peripheral nerve Lesions, Organomegaly, Endocrinopathy, Monoclonal gammopathy, and Skin changes. The prevalence of POEMS syndrome stands at approximately 0.3 per 100,000 individuals . Owing to its low prevalence and the paucity of prospective studies, current treatment approaches largely hinge on retrospective studies and revolve around the use of plasma cell-directed therapy typically used in multiple myeloma treatments. This article presents the pioneering case of utilizing a four-drug combination regimen of DKRd (daratumumab, carfilzomib, lenalidomide, and dexamethasone) as a first-line treatment. This is succeeded by induction therapy and subsequently, autologous hematopoietic stem cell transplantation. A comprehensive review of related literature is conducted.